The Effect of Vaccine Provision on Foreign Policy Public Opinion - Bae, Joonbum; Lee, Changkeun (KDI School of Public Policy and Management, 2022)
What effect does the provision of American vaccines abroad have on views of the US? How does being vaccinated influence opinions regarding foreign aid policy? Does the example of the US providing aid lead to higher support for giving aid in other nations? This paper seeks to answer these questions utilizing original panel data from a two-wave survey fielded in South Korea in 2021 and 2022. It finds that respondents vaccinated with American vaccines, regardless of whether they were donated or procured, did not hold more positive views of the US. However, vaccinated citizens were more likely to support South Korean vaccine aid to other countries, in particular if they received donated shots. Information that the US was supplying aid to developing countries also made it even more likely that vaccinated South Koreans would support their own government giving foreign vaccine aid. While vaccine aid does not improve the donor’s image, this study finds second-order effects that can benefit American interests and facilitate the timely distribution of vaccines across the globe. The results highlight the need to study the indirect effects of vaccine aid and call for broader criteria when evaluating its net effect.
Keywords: Aid; Foreign Policy; Covid-19; Public Opinion